2020
DOI: 10.1155/2020/2638362
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Network Pharmacology and Experimental Validation to Investigate the Mechanisms of Huazhuojiedu Decoction to Treat Chronic Atrophic Gastritis

Abstract: Background. Chronic atrophic gastritis (CAG) is an important stage in the normal gastric mucosa’s transformation into gastric cancer. Huazhuojiedu decoction (HZJD), a Chinese herbal preparation, has proven clinically effective to treat CAG. However, few studies have explored the mechanism of HZJD in CAG treatment. Purpose. This study aimed to shed light on the mechanisms underlying HZJD decoction CAG treatment using a network pharmacology approach and experimental validation. Methods. The active components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…GC comprises the following precancerous steps: chronic active gastritis → chronic atrophic gastritis → gastric intestinal metaplasia → gastric epithelial dysplasia [ 18 ]. Inflammation, cell proliferation and apoptosis, autophagy dysfunction, energy metabolism disorders, and other factors may contribute to the development process, although the exact pathogenesis is still unclear [ 14 , 17 , 19 , 20 ]. The common therapies used for CAG focus on symptomatic treatment and are often not completely effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GC comprises the following precancerous steps: chronic active gastritis → chronic atrophic gastritis → gastric intestinal metaplasia → gastric epithelial dysplasia [ 18 ]. Inflammation, cell proliferation and apoptosis, autophagy dysfunction, energy metabolism disorders, and other factors may contribute to the development process, although the exact pathogenesis is still unclear [ 14 , 17 , 19 , 20 ]. The common therapies used for CAG focus on symptomatic treatment and are often not completely effective.…”
Section: Discussionmentioning
confidence: 99%
“…The use of HZJD is based on turbid toxic syndrome. It functions to clear away heat, and detoxify and invigorate the spleen to remove dampness and has achieved good results in the treatment of CAG [ 14 , 19 ]. However, the regulating effect of HZJD on the intestinal flora is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Makino (Jiaogulan). Previous studies have reported on the possible mechanism of HZJD in the treatment of CAG, which is mainly suggested to be due to the regulation of cell proliferation and apoptosis [ 13 , 14 ]. In a clinical study, we compared the clinical efficacy, gastroscopic efficacy and pathological efficacy of HZJD and ALaTanWuWeiWan for gastric precancerous lesions, and found that the efficacy of HZJD was better than the control group ( P < 0.05), the mechanism was thought to be associated with the decreased expression of HIF-1α, and VEGF and the increased expression of PTEN [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…TCM is a coordinated system for the treatment of multitarget and multicomponent diseases. In a network pharmacology study, we constructed the “herb-compound-target-disease” network diagrams, and found that 156 active ingredients in HZJD had common targets with CAG [ 13 ]. Metabolomics is a systems biology approach that comprehensively describes the pharmacological action of drugs and the association between disease processes and specific biological pathways.…”
Section: Introductionmentioning
confidence: 99%